PENERAPAN PAJAK WARISAN DI BEBERAPA NEGARA - Nina Sabnita (JURNAL INFO ARTHA, 2022)
Inheritance tax is still a controversial discussion. For the state, its objective is more on income redistribution than revenue collection. This research collects information on how inheritance tax is implemented in several developed countries. Japan, Korea, and the UK are countries that still impose inheritance taxes at quite high rates. As with other taxes, the calculation of inheritance tax also has aspects of reduction and exemption. Tax revenue from inheritance tax is indeed very small, on average it is still below 2% of total tax revenue. On the other hand, there is Sweden which has had an inheritance tax for centuries, but then abolished it. In addition to a small portion of revenue, inheritance tax in Sweden can hamper the economy and demotivate people in doing business.